The city council of Lisbon in the Marquis of Pombal enlightened absolutism policy - Fonseca, Teresa (2014)
With this work we intent to analyze the relations between the Lisbon city council – a unique municipality in the national context because of its condition of Portuguese kingdom capital – since the last months of 1764 until the beginning of 1777, on the death of the king Joseph I. In that year, Pombal changed the city counselors election process, their president included. With this measure, the city council could help with much more efficiency the central power to overcome the difficulties of the rebuild of the city, destroyed by the 1755 earthquake and to provide the application of others enlightened absolutism measures, in the place of the Kingdom where they had more visibility and made a more political impact.